Answer:
Statement D is true
Step-by-step explanation:
We should know the following:
x-intercept is the value of x when y = 0
y-intercept is the value of y when x = 0
As shown on the graph, we can deduce the following:
For f(x) : at y = 0 ⇒ x = 1 And at x = 0 ⇒ y = -1
So, for f(x) ⇒ x-intercept = 1 & y-intercept = -1
For g(x) : at g(x) = 0 ⇒ x = -1 And at x = 0 ⇒ g(x) = 1
So, for g(x) ⇒ x-intercept = -1 & y-intercept = 1
Comparing the results with the given options:
A) the x-intercept of f(x) is equal to the x-intercept of g(x) (Wrong)
B) the y-intercept of f(x) is equal to the y-intercept of g(x) (Wrong)
C) the y-intercept of f(x) Is greater than the y-intercept of g(x) (Wrong)
D) the x-intercept of f(x) is greater than the x-intercept of g(x) (true)